2018
DOI: 10.1111/1467-8489.12259
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cost‐effectiveness when environmental benefits are bundled: agricultural water management in Great Barrier Reef catchments

Abstract: Using economic analysis to prioritise improvements in environmental conditions is particularly difficult when multiple benefits are involved. This includes 'bundling' issues in agricultural pollution management, where a change in management action or farming systems generates multiple improvements, such as reductions in more than one pollutant. In this study, we conceptualise and compare two different approaches to analysing cost-effectiveness when varying bundles of benefits are generated for a single project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Attempts have also been made to evaluate the composite performance of wastewater treatment plants by combing economic, environmental and social benefits using analytic hierarchy process (Molinos-Senante et al , 2014). Further, Rolfe et al (2018) proposed two approaches for agricultural water management based on cost-effectiveness. In the first approach, an index was calculated to represent the combined benefits of reduction of different pollutants, which was then compared with the direct costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attempts have also been made to evaluate the composite performance of wastewater treatment plants by combing economic, environmental and social benefits using analytic hierarchy process (Molinos-Senante et al , 2014). Further, Rolfe et al (2018) proposed two approaches for agricultural water management based on cost-effectiveness. In the first approach, an index was calculated to represent the combined benefits of reduction of different pollutants, which was then compared with the direct costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is evidence from various reviews (e.g., Pannell & Roberts, 2010) that much more could be achieved if available funds could either: (a) be better prioritized at the program and project level or (b) provide stronger incentives for change. As one example, researchers estimate that environmental outcomes for Australian Great Barrier Reef management could be doubled if existing funds could be allocated more efficiently (Rolfe et al, 2018b). However, conservation tenders see very low rates of adoption despite recommendations by economists and high profile examples (Bingham et al, 2021).…”
Section: Problemmentioning
confidence: 99%
“…Not applied at present Currently most efforts to protect the GBR are provided by government through: (a) regulatory mechanisms, such as zoning the GBR into different use areas, including green zones, (b) governance arrangements, including the establishment of the Great Barrier Reef Marine Park Authority and Natural Resource Management groups in key catchments draining into the GBR, and (c) funds, largely through grant programs to encourage primary producers to reduce pollutants leaving farms and properties. Beher et al (2016) and Rolfe et al (2018) have identified that these grant programs are not very efficient, recommending that better ways to prioritise and allocate funding be identified. The use of water quality tenders and other auction mechanisms to allocate public funds are one approach to improving cost effectiveness (Rolfe and Windle, 2011b), as are efforts to prioritise where public funds are best invested (Star et al, 2018).…”
Section: Taxes On Pesticides and Chemical Fertilisersmentioning
confidence: 99%